Extraintracranial Bypass as a Rescue Therapy for Symptomatic Flow Diverter Thrombosis - Luigi A. Lanterna; Alessandro Lunghi; Carlo Brembilla; Paolo Gritti; Claudio Bernucci (Case Reports in Neurological Medicine)
A 56-year-old female with a giant partially thrombosed unruptured carotid-ophthalmic aneurysm was treated with a Pipeline flow diverter. Three months after the procedure, in concomitance with the discontinuation of one of the antiplatelet medications, the patient suffered from a minor stroke and relapsing transient ischemic attacks. The angiography demonstrated the occlusion of the internal carotid artery, and a perfusion-weighted CT scan showed a condition of hypoperfusion. The patient underwent a double-barrel extraintracranial bypass. The postoperative course was uneventful and she has experienced no further ischemic events to date.